PENGARUH PENINGKATAN HARGA LAHAN TERHADAP PERKEMBANGAN PROPERTI KOMERSIAL DI SEGITIGA PERUMDA TEMBALANG SEMARANG - Palupi, Kartika Dwi (Jurnal Pengembangan Kota, 2013)
Tembalang is a growing area with a central activity of education. The existence of educational functions have an impact to presence various activities in the surrounding, particularly for support the main functions of the education. The emergence of a variety of activities such as trade and services, housing, and higher education highly influential on increasing demand for land in this region. Land is Â limited goods will increase the price comparable with the increasing demand. The higher land demand occurs during the relocation of the first Undip Campus (located in Pleburan) to a new campus in Undip Tembalang which resulted in an increase land prices more than 1.000%. The price of land which originally ranged from Rp 200,000, - until Rp300.000, -/ m2 jumped to Rp.3.500.000,- until Rp4.000.000,-/ m2 (http:/www.antarajateng.com, accessed 2 November 2010). Segitiga Perumda is a very strategic location, is also supported by the completeness of facilities and infrastructure, as well as adequate accessibility. This condition is very support of investment in this region thus causing an increase in land prices significantly from year to year. Under these conditions, Semarang City establish the presence of the UN revised each year in which are also NJOP Earth. The rise of the United Nations addressed to over the function property into commercial property to increase value added as well asm the ability to pay. To achieve the objectives of the study, carried out a visit at an early stage to obtain data instansional Earth NJOP in the Segitiga Perumda for seven year (2005-2011) is the reference for analyzing land prices. Earth NJOP become as a reference because of the difficulty to getting the real land price data in time series (2005-2011).The data used to map the Earth NJOP region based on land prices. Furthermore, field observations and interviews conducted to determine the function of existing properties in the Segitiga Perumda by type of commercial property. From both, carried out in order to obtain super-impose an overlay map associated cost of land and commercial property development in 2005-2011. To determine the significance of the influence of increasing land prices to the development of commercial properties, the calculations performed by linear regression analysis using SPSS software version 17.0. Based on these statistics, it is known that the effect of land prices to the development of commercial properties for 89.05%, or have been in accordance with the initial hypothesis of the study. Based on the analysis, it can be concluded that an effect between the increase in land prices to the development of commercial properties in the Segitiga Perumda Tembalang. Land prices also determine the type of commercial property developments. On high land prices, growing commercial property is a business with high accessibility requirements, such as photocopy, supermarket, and retail outlets. Boarding commercial property and lodging accessibility needs are not so high that tends to develop in the zone of the cheaper land prices. Recommendations in this study aimed to Semarang City Government relating to policy Â formulation RDTRK and zoning district and the control of a business license.Recommendations for the Segitiga Perumda Tembalang is by controlling and pegawasan commercial property.